2008
DOI: 10.1080/00288230809510461
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus in humped and hollowed soils of the Inchbonnie catchment, West Coast, New Zealand: I. Variation with age and distribution

Abstract: Phosphorus (P) is the limiting nutrient for eutrophication of Lake Brunner in the South Island of New Zealand. Dairy farms within the Inchbonnie catchment are thought to be a major source of P that enters the lake. A study was conducted using farm surveys and sequential P fractionation to investigate and account for the fate, form and concentration of P in the 0-7.5 cm layer of hump and hollow land of different ages (1-13 years since development). Data indicated that, apart from two labile organic P fractions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Of the factors that could be managed on dairy farm paddocks, decreasing the P lost from fertiliser and improving the P retention capacity of the soil are two that have been highlighted as simple and potentially costeffective (McDowell 2008b). Methods to decrease P lost from fertilisers have focused on using fertilisers with little water-soluble P (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Of the factors that could be managed on dairy farm paddocks, decreasing the P lost from fertiliser and improving the P retention capacity of the soil are two that have been highlighted as simple and potentially costeffective (McDowell 2008b). Methods to decrease P lost from fertilisers have focused on using fertilisers with little water-soluble P (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Biennial assessments showed that soil physical and biological quality can generally be considered good despite the very wet conditions and the intensive farming operations within the catchment. An exception was the measured soil Olsen P concentrations (Table 1), which increased over time beyond the optimum concentration of 25-30 mg L À1 required for pasture production (McDowell 2008b). These enriched concentrations are uneconomic and pose increased risk of P loss in surface runoff to waterways.…”
Section: Farm Surveysmentioning
confidence: 99%
“…The large losses of P for the Inchbonnie catchment (compared with dairy farms outside of the West Coast region) can be attributed to the combination of high source and transport risk factors for P loss from the dairy farms. Source risk factors include the regular inputs of fertiliser P to maintain an enriched soil Olsen P concentration, a soil type with poor P retention (McDowell 2008b), stock stream crossings and runoff of farm dairy effluent (FDE) from the hump-and-hollow land forms common to the dairy farms in the catchment. Leakage from FDE storage or treatment ponds was another potential source risk factor, but one that was difficult to quantify.…”
Section: Surface Water-groundwater Interactionmentioning
confidence: 99%
“…Paddocks examined in the Lake Brunner catchment in 2006 had been humped and hollowed from 1 to 13 years ago, suggesting that the amount of land contoured into humps and hollows has increased since the early 1990s (McDowell 2008a). Extensive humping and hollowing has led to concern that nutrients are drained faster to the lake and that increased agricultural runoff from dairy farms in particular may affect the lake's water quality.…”
Section: Introductionmentioning
confidence: 99%
“…Average annual rainfall in the Lake Brunner catchment is 3-7 m year À1 , and in order to enhance drainage of ponded surface water, farmers contour the land into long ridges with hollows between, a process known as 'humping and hollowing' (Brown 2004;McDowell 2008aMcDowell , 2008b. Paddocks examined in the Lake Brunner catchment in 2006 had been humped and hollowed from 1 to 13 years ago, suggesting that the amount of land contoured into humps and hollows has increased since the early 1990s (McDowell 2008a).…”
Section: Introductionmentioning
confidence: 99%